A critique of grading: Policies, practices, and technical matters - Anderson, Lorin W. (Education Policy Analysis Archives, 2018)
In recent years there was been a raft of criticisms of the way that grades (or marks) are assigned to students. The purpose of this paper is to examine the strengths and weaknesses of grading systems and grading practices, drawing upon both historical and contemporary research and writing. Five questions are used to frame the review and organize the paper. They are: (1) Why do we grade students? (2) What do grades mean? (3) How reliable are students’ grades? (4) How valid are students’ grades? and (5) What are the consequences of grading students? The results suggest that (1) The are several purposes for grading students; the way that grades are assigned and reported should be consistent with the specified purpose. (2) Grades mean different things to different people (including the teachers who assign them). (3) Grades on a single task (e.g., a test or project, a homework assignment) are quite unreliable, whereas cumulative grades (that is, those based on several data sources) are reasonably reliable. (4) The validity of grades on a single task is virtually impossible to determine; however, the evidence suggests that cumulative grades are reasonably valid. (5) Grades influence a variety of student affective characteristics (e.g., self-esteem). However, their influence is no greater, nor less than, a host of other school-related factors.